Aesthetic Reduction in Narration and Immersion in the Latest German and Polish Debut Novels - BADURA, Bożena Anna (Transfer. Reception Studies, 2017)
The paper investigates the occurrences and characteristics of the language used in contem-porary German literature and how these enact influence on immersion (Ryan). Through a discussion of the empirical approach to the process of reading, the article distinguishes between the aesthetic reduction of today and the long descriptive characteristics found mostly in older works of literature. For the majority of the newest works of contemporary literature, the analysis finds there is a positive influence towards both the cognition of the text and the immersion of the reader with the piece of literature.